2013
DOI: 10.1007/s10753-013-9773-1
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Gene Polymorphism is Associated with Susceptibility to Leprosy by Affecting Inflammatory Cytokines

Abstract: Autophagy and inflammation closely interact with each other, and together, they play critical roles in bacterial infection. Leprosy is caused by the infection of Mycobacterium leprae (M. leprae). The objective of the study was to investigate the association between polymorphisms in IRGM, an autophagy gene, and susceptibility to leprosy, and identify possible functions of the polymorphism in the infection of M. leprae. Two polymorphisms in IRGM, rs4958842 and rs13361189, were tested in 412 leprosy cases and 432… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 23 publications
0
41
0
1
Order By: Relevance
“…These findings indicated the involvement of autophagy or phagocytosis in leprosy pathogenesis. Moreover, two other genes that regulate autophagy, LRRK2 and IRGM, were found to be associated with leprosy (109,110). In a zebrafish model, the LRRK2 mutant showed a weakened immune response to Mycobacterium marinum infection, functionally confirming the role of LRRK2 in infectious diseases (111).…”
Section: The Hereditability Of Leprosy Genetic Risk Factors Associatimentioning
confidence: 79%
“…These findings indicated the involvement of autophagy or phagocytosis in leprosy pathogenesis. Moreover, two other genes that regulate autophagy, LRRK2 and IRGM, were found to be associated with leprosy (109,110). In a zebrafish model, the LRRK2 mutant showed a weakened immune response to Mycobacterium marinum infection, functionally confirming the role of LRRK2 in infectious diseases (111).…”
Section: The Hereditability Of Leprosy Genetic Risk Factors Associatimentioning
confidence: 79%
“…This is required to permit immune tolerance, and the inability for adaptive immune cells to recognize these self-antigens can result in an autoimmune response that promotes inflammation and cell death. Therefore LRRK2-dependent ALP deficits could result in autoimmune dysregulation, as suggested for inflammatory disorders such as Crohn’s disease, colitis, and leprosy (Wellcome Trust Case Control Consortium, 2007; Henckaerts et al, 2011; Jostins et al, 2012; Yang et al, 2014). Indeed, co-morbidity between Parkinson’s disease and Crohn’s disease indicates that people diagnosed with PD could suffer from this dysregulation within the periphery, evidence for the potential involvement of the immune system as a player in vulnerability of PD, as well (Nalls et al, 2014).…”
Section: Influence Of Autophagy In the Immune Systemmentioning
confidence: 99%
“…leprae -containing double-membrane vacuoles in mouse MΦs, a hallmark of autophagosomes, suggesting a possible involvement of autophagy in the immunomodulatory response of the disease [27,28]. It has also recently been suggested that the IRGM gene polymorphism, which is linked with the susceptibility to tuberculosis [29], is associated with an increased risk of developing leprosy by affecting the production of inflammatory cytokines such as IFN-γ [30]. Furthermore, upregulation of IRGM was seen in M .…”
Section: Introductionmentioning
confidence: 99%